Maximizing Green Infrastructure in a Philadelphia Neighborhood - Zidar, Kate (2017)
While the Philadelphia Water Department (PWD) is counting on Green Stormwater Infrastructure (GI) as a key component of its long-term plan for reducing combined sewer overflows, many community stakeholders are also hoping that investment in greening can help meet other ancillary goals, collectively referred to as sustainable redevelopment. This study investigates the challenges associated with implementation of GI in Point Breeze, a residential neighborhood of South Philadelphia. The project team performed a detailed study of physical, social, legal, and economic conditions in the pilot neighborhood over the course of several years, culminating in the development of an agent-based model simulation of GI implementation. The model evaluates a) whether PWD’s GI goals can be met in a timely manner, b) what kinds of assumptions regarding participation would be needed under different theoretical GI policies, and c) the extent to which GI could promote sustainable redevelopment. The model outcomes underscore the importance of private land in helping PWD achieve its GI goals in Point Breeze. Achieving a meaningful density of GI in the neighborhoods most in need of sustainable redevelopment may require new and creative strategies for GI implementation tailored for the types of land present in those particular communities.